A Comparative Study on Utilization of Palm Oil Fuel Ash (POFA) as Partial Cement Replacement in Concrete - Abdul Hamid, Noor Azlina; Hamsan, Nabil Farhan (Recent Trends in Civil Engineering and Built Environment, 2021)
Palm oil is Malaysia’s most significant crop which has helped transform its agricultural and economic scenario. Despite the apparent benefits, the palm oil mill also contributes significantly on environmental degradation, both at the input and output sides of its operations. Palm oil fuel ash (POFA) is one of waste materials from palm oil mills. The existing of POFA is eventually in desperate need to be beneficially used. This study was investigated the utilization of POFA as partial cement replacement in concrete. The objective of this study is to identify the workability and compressive strength performance of concrete containing POFA and to determine the optimum percentage of POFA as partial cement replacement in concrete. The performance of concrete on workability and compressive strength was determined and analysed based by previous studies on the use of POFA as partial cement replacement in concrete. About 35 previous research paper were reviewed and compared in term of experimental results in order to fulfill the objective of this study. Based on the review analysis, it can be concluded that the utilization of POFA can affect the workability and compressive strength of concrete differently with different type of concrete. It was found that an optimum percentage of POFA in range of 5% to 40% can enhance the properties of various type of concretes in terms of workability and compressive strength.